Performing Race(d) music in Central Europe: Can Bluegrass be "Ethnically Czech"? - Bidgood, Lee (Lidé města, 2009)
The 1993 Česko-Slovenský split was the latest step in the formation of today’s nearly mono-ethnic Czech nation-state, a culturally homogeneous milieu where ethnicity blurs with citizenship, and outsiders are not always welcomed. As a phenotypically “white” scholar engaged in participatory observation of Czech performance of bluegrass music, I feel the power of music to forge identity in this exclusive environment: my “Americanness” both endears me to and distances me from my Czech colleagues and the life of their communities. Bluegrass’s foundations in U.S. minstrelsy, its connections with pro-Anglo rhetoric, and its troubling “whiteness” in sound and effect give me pause as I consider how bluegrass musical practices are reproduced in the Czech Republic. Bluegrassers perform repertory and style that is part of the Afro-American musical tension: enhanced by cultural hybridity, but also complicated by legacies of identity and power. How do Czechs process the American black / white tension when they recreate its sounds within very different demographic and socio-historical conditions? The appearance of the Confederate battle or “rebel” flag and controversial repertory in Czech bluegrass is less important in this discussion than group dynamics and discourse that evoke many of the unmarked categories outlined in current American “whiteness” literature. The “minority” rhetoric voiced by Czechs as a small part of the European conglomerate, and as members of the local bluegrass subculture clash with their de facto majority status within the bounds of the Czech state and within the bluegrass community. By describing some of the groups and events I have observed this year in the Czech Republic, I will give a sense of the “Czechness” that is built into Czech performances of country and bluegrass, and discuss the implications of these intersections of music, identity, and performance.